2022
DOI: 10.1007/s00167-022-07211-z
|View full text |Cite
|
Sign up to set email alerts
|

Anterior talofibular ligament remnant quality is important for achieving a stable ankle after arthroscopic lateral ankle ligament repair

Abstract: Purpose The relationship between ligament remnant quality and postoperative outcomes after arthroscopic lateral ankle ligament repair for chronic lateral ankle instability is controversial. This study aimed to determine whether the signal intensity of the anterior taloibular ligament on preoperative magnetic resonance imaging and ligament remnant quality identiied on arthroscopy are associated with recurrent ankle instability after arthroscopic lateral ankle ligament repair. Methods A total of 68 ankles from 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Poor quality of ATFL remnant could result in significantly higher recurrent instability because the ATFL has been replaced by scar tissue. 43 In the current study, the ATFL remnant quality in the recurrence group was often poorer than that in the nonrecurrence group. The quality of the remnant can be predicted by thin-slice MRI signal intensity preoperatively.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Poor quality of ATFL remnant could result in significantly higher recurrent instability because the ATFL has been replaced by scar tissue. 43 In the current study, the ATFL remnant quality in the recurrence group was often poorer than that in the nonrecurrence group. The quality of the remnant can be predicted by thin-slice MRI signal intensity preoperatively.…”
Section: Discussionmentioning
confidence: 46%
“…23 It is difficult to define the recurrence of the instability after surgery. Yoshimoto et al 43,44 defined recurrent instability as ankle resprain after surgery. In this study, recurrent instability was defined as a postoperative TTA of ≥6 degrees because it is reported that a normal TTA was <5 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…25,28,41 Unlike the ATFL, the CFL is an extracapsular ligament that is difficult to completely repair arthroscopically. 27,45 The combined injury of ATFL and CFL produces more severe damage than a single injury, 27 and an additional arthroscopic augmentation did not improve the outcome. 45 Because of the difficulty in arthroscopic repair of the CFL, many surgeons who attempt complete arthroscopic surgery alone are likely to perform reconstruction using a tendon graft for all ankles, except in cases of isolated ATFL injury.…”
Section: Discussionmentioning
confidence: 94%
“…27,45 The combined injury of ATFL and CFL produces more severe damage than a single injury, 27 and an additional arthroscopic augmentation did not improve the outcome. 45 Because of the difficulty in arthroscopic repair of the CFL, many surgeons who attempt complete arthroscopic surgery alone are likely to perform reconstruction using a tendon graft for all ankles, except in cases of isolated ATFL injury. In our opinion, this may be overtreatment for combined injuries of the ATFL and CFL with remnants.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation